Neuromuscular disorder as initial manifestation of secondary hyperparathyroidism - a case report - Karim Hajjar; Tim Hagenacker (PAGEPress Publications, 2017)
This case report describes a young woman who presented with slowly progressing weakness of the proximal limb muscles and slight decrease of muscle tone but otherwise unremarkable neurological history. Diagnostic workup revealed fatty degeneration of the girdle muscles and an excessive increase of the parathyroid hormone as a result of severe vitamin D deficiency. Secondary hyperparathyroidism was diagnosed, and neurological deficits resolved after treatment of the underlying endocrinopathy.